Performance control during longitudinal activation fMRI studies - Lotze, Martin (Frontiers in Human Neuroscience, 2024)
The documentation of performance during functional imaging represents a standard procedure employed to control for compliance, sensorimotor and cognitive demand. In the case of motor tasks, preciseness, force and frequency have a significant impact on the functional activation magnitude. Questionnaires are employed in psychological investigations to control for cognitive demand, while psychophysiological documentation is used to record bodily responses. For longitudinal intervention studies, it is of utmost importance to implement a meticulous pre-and post-performance control and balance in order to accurately assess changes over time. Any changes in compliance may introduce an additional uncontrolled variable, which may hinder the interpretation of fMRI-related changes. This narrative review will present strategies for controlling and balancing performance in functional imaging approaches to document neuroplasticity in rehabilitative studies. These include motor related aspects such as precision, velocity, force, but also timing aspects such as start and stop of movement periods. Additionally, it will discuss strategies for the modulation and control of movement aspects with visual feedback, as well as for the control of physiological changes during experimental modulation. Although these measures require additional care, which is often more demanding than the neuroimaging part of the study, they are crucial for a relevant interpretation and publication of fMRI studies.